Midlatitude propagation of VLF to MF waves through nighttime ionosphere above powerful VLF transmitters. Issue 3 (12th March 2013) - Lefeuvre, F.; Pinçon, J. L.; Parrot, M.
Abstract: [1] Midlatitude nighttime observations made by the DEMETER satellite in the very low frequency (VLF) to medium frequency (MF) bands (3 kHz to 3 MHz) have demonstrated the propagation of radio waves from the bottom of ionosphere up to the satellite altitude (~700 km). Propagation characteristics derived from the magneto‐ionic theory [Budden, 1985 ] are used to explain the absence of wave observations between ~1 and 2 MHz. Under hypotheses made for the Appleton and Hartree (or Appleton and Lassen) formula, studies of the vertical variations of the real and imaginary parts of the refractive index are performed to point out modifications in the propagation characteristics of the waves: (i) at the crossing of the plasma cutoffs regions, (ii) at the crossing of the ordinary and extraordinary mode resonance regions, and (iii) in the region where the product of the collision frequency ( ν ) and the electronic density (Ne) is maximum. It is shown that enhancements in the collision frequencies, produced by powerful VLF transmitters in the region where the product of ν and Ne is maximum, open the half angle of the MF wave transmission cones and increase the power densities of those waves at the DEMETER altitude. Key Points: New region of VLF heating in the F‐layer wave propagation controlled by transmission cones at the X=1 plasma cut‐offs enhancements in collision frequencies open the transmission cones